Tourism destination development in the context of brand personality and advertising message : a case study of Swedish Lapland, ecotourism perspective - Lohela, Miia-Ilona (2008)
Tourism is growing globally. During the last years, the development of tourism in Sweden, especially in the county of Norrbotten, has been positive. A destination marketing organisation, DMO, Swedish Lapland was established in 2001 and is responsible for marketing tourism in the county of Norrbotten. The purpose of this thesis was to gain better understanding of how DMOs that represent ecotourism develop destinations in the context of brand personality and advertising message. The following research questions were addressed in order to reach the purpose: How do DMOs develop tourism destinations?, How do DMOs create brand personality?, and How do DMOs incorporate brand personality into the advertising message? The study started with a literature review which was used as a base for problem discussion and theory. The review of the theory resulted as a conceptual framework, which in turn was used as a base for the formulation of the interview questions. The primary data was collected during the interview with Swedish Lapland’s Managing Director. This study indicates that cooperation between different industries is important in order for a destination to be able to develop. In addition, the study shows that a destination’s development does not necessarily have to lead to increasing numbers of visitor in order for the destination to become successful in terms of financial or popularity aspects. Furthermore, brand development is a large part of destination development from the marketing perspective. A destination brand personality is strongly connected to the brand’s core values, which is then communicated to target markets through logos, slogans, images, brand concepts and themes. Finally, it is important for the members of the DMO to build their business and marketing activities around the DMO’s overall branding strategy in order for the DMO to be able to communicate a coherent advertising message. Metaphors are used in advertising messages in order to portray destination brand personality. Validerat; 20101217 ...